Leadership the Barack Obama way : - Leanne, Shelly. (McGraw-Hill, 2010)
In his historic rise to the most powerful position in the world, Barack Obama single-handedly altered the concept of leadership around the world. Now, Shel Leanne—the expert on the Obama way of leadership—explains how to thrive in any business setting by adopting the same skill set. Leadership the Barack Obama Way examines the ins and outs of the leadership style the President of the United States rode to heights of power nobody dreamed possible just a short time ago. Leanne breaks down Obama’s style into easily digestible pieces that you can apply in any situation.